Recent developments in African financial markets: Agenda for further research - Aryeetey, E. (Journal of African Economies, 2003)
Despite the massive expansion in global financial markets in the 1990s, this development was felt only marginally in Africa. The lack of comparable expansion and impact in the African financial markets was observed after several years of financial sector reforms in many countries. Following these developments, several questions can be raised about what the most appropriate reforms should be. It is obvious that while the taking over of the financial markets by the state, as happened before reforms, cannot be the best means to make finance respond to the developmental needs of poor economies, outright liberalisation of markets with significant institutional and structural inadequacies also cannot lead to the desired outcomes. This is clearly shown by the African experience of the 1980s and 1990s. Are there alternatives to these two approaches of managing financial systems and markets? Clearly, greater research needs to be undertaken into what the peculiar policy and institutional needs of these financial markets are, taking into account the structures of economies, and learning from recent developments in theory. © Centre for the Study of AfricanEconomies 2003; all rights reserved.